Assessment of residential load profiles and demand response potential for a renewable-based microgrid : a case study of auroville township in India - Miriyala, Yogitha; Singh, Jai Govind; Salam, P. Abdul; Weerakorn Ongsakul; Energy Faculty; Asian Institute of Technology Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
High capacities of variable renewable energy are expected to be grid-integrated in India by 2030 to mitigate climate change. This will pose new challenges for grid operators and, among other strategies, will call for high demand flexibility. Demand response (DR) has the potential to provide these flexibility services. With the projected increase in appliance ownership, residential energy consumption will increasingly contribute to peak load. Thus, this study aims to estimate the generation, storage and distribution capacity benefits of introducing residential DR to achieve 100% integration of net renewable energy in a community{u2019}s microgrid. The case study is a region in Auroville, India, comprising 100 households. Firstly, the distribution transformer (DT) and appliance-wise load profiles are generated for 2022 using metered time-series data and a survey conducted in Auroville. Then, based on future appliance ownership rates, population growth, and appliance efficiency improvements, the DT and appliance-wise load profiles are projected for 2030. Secondly, using a DR algorithm that considers appliance-specific DR factors and appliance-wise load profiles, the modified DT load profiles with DR are generated and the technical potential of DR is assessed. Lastly, the microgrid is designed for the DT load profiles with and without DR and a financial analysis is conducted. The technical potential of DR under the highest and lowest DR potential scenarios were 20.7%, and 8.1%, respectively. The DR scenario, including only air conditioners and electric vehicles, termed DR_EV&AC, was the most financially attractive scenario with a technical potential of 15.2%. The reduction in NPC between DR_EV&AC and the scenario without DR was 3.2%. The LCOE for DR_EV&AC was 11.49 {u20B9}/kWh and 10.38 {u20B9}/kWh, respectively, for maximum and minimum system capital cost (SCC) scenarios. The avoided cost of energy from DR_EV&AC was 0.27 {u20B9}/kWh. ROI for maximum and minimum SCC scenarios were 30.93 and 35.26, respectively. Supposing these benefits were translated into incentives paid to the customers enrolled in DR programs, the share of the incentive to their average monthly bill was estimated at around 20.3%, which is attractive. Thus, this study demonstrated the potential of residential DR in Auroville, India.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science Sustainable Energy Transition
Thesis (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Microgrids (Smart power grids) -- India; Renewable energy sources -- India